Pengalaman Manajemen Nyeri Kronis pada Pasien Gagal Ginjal Kronis yang Menjalani Hemodialisa : Studi Kualitatif - Kartika, Imelda Rahmayunia; Rezkiki, Fitrianola (Journal of Pubnursing Sciences, 2025)
Background: Chronic pain is a common and distressing experience for patients with end-stage renal disease (ESRD) undergoing hemodialysis, yet its complexity and management remain insufficiently explored. Understanding how patients perceive and manage this pain is crucial for developing holistic nursing interventions. Aim: To explore the lived experiences of chronic pain management among patients receiving long-term hemodialysis. Method: A qualitative descriptive approach was employed, using in-depth semi-structured interviews with a purposive sample of hemodialysis patients. Data were analyzed thematically to identify core patterns and meanings. Results: Three themes emerged: (1) perceived meaning and impact of pain during hemodialysis, reflecting patients’ physical discomfort, emotional distress, and disruption of daily life; (2) patterns and characteristics of pain, described as fluctuating in intensity, duration, and location throughout the hemodialysis process; and (3) complementary and supportive strategies for pain management, including spiritual practices, relaxation, distraction techniques, and reliance on family support. The findings underscore that pain during hemodialysis is not only a physical phenomenon but also a psychosocial and spiritual challenge. Nurses play a pivotal role in recognizing patients’ multidimensional pain experiences and in integrating complementary approaches alongside conventional care. Conclusion: This study highlights the importance of patient-centered, culturally sensitive strategies to enhance pain management and quality of life in ESRD care. It is recommended that future nursing practice and policies incorporate complementary therapies and patient education programs to strengthen pain management strategies in hemodialysis units.